Joan of Arc: a study in virginal power and female autonomy - Jewkes, Steven (My University, 2025)
This work examined the life of Joan of Arc a visionary and military leader from fifteenth-century France through contemporary records and later post-humous interpretations by admirers and detractors alike to determine if Joan was able to achieve autonomy in her brief career and if so by what methods. Using these resources it argues that Joan was clearly able to achieve an unprecedented level of political and military autonomy for a common woman in fifteenth-century Europe by using the holy notions of virginity and divine connection that has allowed many mystics and visionaries to ascend beyond their stations throughout history. Furthermore it considers the gendered notions of clothing that were clearly at play as many considered Joan to be ‘dressing as a man’ and changing her identity to achieve her goals an argument that this paper disagrees with based on the evidence.
Presented on February 28th, 2025, at MacEwan University Humanities Department Undergraduate Research Showcase, and on April 17, 2025, at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: Joan of Arc; female autonomy